Pengembangan Reading Comprehension Siswa Melalui Media Pembelajaran Aplikasi Quizizz Di MA Nurul Huda Sukaraja - Mutiara Triadinda; Nasyiatul Asiyah; Usman Efendi; Ma’rifatul Anwar (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
This Community Service aims to provide learning media training using the Quizizz application on reading comprehension. Reading comprehension lessons are often a problem in English subjects, because in addition to having to read the text students also have to understand the reading text. To make it easier for students to understand the content contained in the reading text easily, Media is needed so that they have a high enthusiasm for learning in doing and understanding the English lesson questions. The subjects in this service are class XI science students totaling 18 students. This service implementation activity uses the audience center method, namely by providing interactive training and mentoring. The implementation of training on the use of the Quizizz application is designed in several stages, namely: planning, implementation, follow-up, and evaluation. The result obtained from this service activity is that students can use the Quizizz application as a learning medium in reading comprehension material.